The Influence of Workload on Job Satisfaction With Job Stress as a Mediating Variable : A Study on Employees of PT. BPR Karya Artha Sejahtera Indonesia - Nethania Clara Yashinta; Made Surya Putra (International Forum of Researchers and Lecturers, 2025)
The purpose of this study is to examine and explain the influence of workload on job satisfaction with job stress as a mediating variable at PT. BPR Karya Artha Sejahtera Indonesia. This research employs a quantitative causality approach with a sample of 86 respondents selected using a saturated sampling technique. Data were collected through questionnaires and analyzed using inferential analysis with the SEM-PLS (Structural Equation Modeling – Partial Least Squares) method through the SmartPLS version 4.0 software. The results indicate that workload has a positive effect on job stress and a negative effect on job satisfaction. Job stress has a negative effect on job satisfaction and is proven to mediate the relationship between workload and job satisfaction. These findings support the two-factor theory and emphasize that poorly distributed workload can cause employees to experience stress at work. Job stress can reduce employees’ satisfaction with their jobs. This study is expected to provide practical contributions to the research site in improving job satisfaction by considering workload and job stress.